Weathered Coal-Immobilized Microbial Materials as a Highly Efficient Adsorbent for the Removal of Lead - Zile Jiao; Chunhua Gao; Jianhua Li; Jinjing Lu; Juan Wang; Lin Li; Xiaojing Chen (Molecules, 2024)
Most research on immobilized microorganisms employs biomass charcoal as a carrier, but limited studies explore coal-based resources for microbial immobilization. Herein, lead-resistant functional strains were immobilized using weathered coal as a carrier, resulting in the development of a weathered coal-immobilized microbial material (JK-BW) exhibiting high efficiency in lead removal from solutions. A quadratic polynomial model for the adsorption capacity and adsorption rate of JK-BW on Pb2+ was developed using the Box-Behnken method to determine the optimal adsorption conditions. The Pb2+ adsorption mechanism of JK-BW was studied through batch adsorption and desorption experiments along with SEM-EDS, BET, FT-IR, and XPS analyses. Findings indicated that optimal conditions were identified at 306 K temperature, 0.36 g/L adsorbent dosage, and 300 mg/L initial solution concentration, achieving a peak adsorption performance of 338.9 mg/g (308 K) for the immobilized material, surpassing free cell adsorption by 3.8 times. Even after four cycles of repeated use, the material maintained its high adsorption capacity. Pb2+ adsorption by JK-BW involved monolayer chemisorption with ion exchange, complexation, precipitation, physical adsorption, and microbial intracellular phagocytosis. Ion exchange accounted for 22–42% and complexation accounted for 39–57% of the total adsorption mechanisms, notably involving exchanges with K, Ca, Na, and Mg ions as well as complexation with –OH, –COOH, CO–OH, –COOH, CO–, NH2, and the β-ring of pyridine for Pb2+ adsorption.